Analisis Faktor yang Mempengaruhi Non Performing Loan pada Bank Perkreditan Rakyat di Nusa Tenggara Barat - Zamri, Yati Fitria; Handajani, Lilik; Rifai, Ahmad (E-Jurnal Akuntansi, 2020)
This study aims to provide empirical evidence about  main cause of height Non Performing Loan (NPL) at Rural Bank in West Nusa Tenggara. The methodology used is Factor Analysis exploratory . Population in this research is all Rural Bank  in West Nusa Tenggara. Total Respondent are 128 respondent which are Board Director, Marketing department, and Collection Department. Based on previous research found 38 variabel that causes NPL at Rural Bank. By using analysis factor  the study found 10 major factors as the main cause of the NPL at Rural Bank in West Nusa Tenggara. The results of this research can be used as a reference for Rural Bank  in an attempt to suppress the NPL in each Rural Bank. In addition, it can be used as a reference for financial Services Authority (OJK)  in the surveillance institution to BPR. Keywords: Non Performing Loan; Rural Bank; Factors Analysis; Main factor.